Validation of Kvaal's and Cameriere's methods of age estimation in people of Marathwada origin - Maneesha Das; Abhishek Singh Nayyar; Neetu Punhani; Harsha Puri; Rakesh Rohilla; K V Chalapathi; B Anand Babu (Wolters Kluwer Medknow Publications, 2017)
Context: Aging, in forensic context, is necessary both for the dead and the living. Kvaal et al. introduced a method of age estimation by indirectly measuring secondary dentin deposition on radiographs. Cameriere et al., later, put forth a method based on radiographic estimation of pulp/tooth area ratio (AR) in specific teeth of the dentition. Aim: The purpose of the present study was to assess the validity of Kvaal's and Cameriere's methods of age estimation in a specific populace of Marathwada origin. Materials and Methods: A total number of 110 patients aged between 15 and 75 years were selected and the variables P = complete pulp length/root length (from enamel-cementum junction [ECJ]-root apex), r = complete pulp length/complete tooth length, a = complete pulp length/root width at ECJ level, b = pulp/root width at midpoint level between ECJ level and mid-root level, and c = pulp/root width at mid-root level; and pulp/tooth AR were recorded as devised in Kvaal's and Cameriere's methods of age estimation, respectively. Statistical Analysis: Statistical analysis was performed with SPSS (version 10.5) package. Mean comparison of morphological variables was carried out using Student's t-test. Intra- and inter-observer reproducibility of measurements was studied using the concordance correlation coefficient. Results: Of all the morphological variables, variables P, r, mean (M), length (L), and pulp/tooth AR of Kvaal's and Cameriere's methods correlated significantly with age with variable P correlating the best among them. Conclusion: Variables associated with width ratios rather than length ratios of Kvaal's and Cameriere's methods correlated best with chronological age in the populace of Marathwada origin.